Comparative Study of Murabahah Contract Recording Practices: Implementation at Qurrata Ayun Sharia Cooperative versus PSAK 402 Standards - Diatul Fajri; Farid Ahmad Marlion; Qumil Laila Arham; Winda Wulansari; Husni Shabri (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
Background. Implementing Murabahah accounting in compliance with national standards poses a critical challenge for sharia cooperatives as pillars of inclusive microfinance in Indonesia. The dominance of Murabahah financing, accounting for 69% of sharia financing portfolios, is not matched by adequate accounting standard implementation capacity at the cooperative level. Purpose. This qualitative study aims to analyze the conformity of Murabahah accounting practices at Qurrata Ayun Sharia Cooperative with PSAK 402 provisions and identify impeding factors. Method. This study uses an instrumental case study qualitative approach at the Qurrata A'yun Sharia Cooperative. Data was collected through triangulation: analysis of 45 murabahah transaction documents (2022-2023), observation, and semi-structured interviews with 8 key informants (managers, accounting staff, administrators, and the sharia supervisory board). Data analysis was conducted thematically and comparatively with PSAK 402, with validity maintained through triangulation and member checking. Results. Findings reveal partial adherence to basic sharia accounting principles, such as separating principal financing and margins via Deferred Revenue mechanisms, but technical gaps exist in inventory treatment and cost of goods sold structure. Primary constraints are the lack of specialized sharia financial reporting training and reliance on manual recording systems. Conclusion. PSAK 402 implementation in sharia cooperatives constitutes an evolutionary process requiring phased approaches and multi-stakeholder collaboration. The proposed solution framework from standard chart of accounts development and staff capacity enhancement to simple technology adoption provides a practical roadmap for improving transparency and accountability in sharia microfinance institutions to support Indonesia's inclusive economic development.